PENERAPAN SISTEM INFORMASI PENJADWALAN KARYAWAN MENGGUNAKAN VISUAL BASIC STUDIO 2010 - AYU ARIANDI, FISKA; OKTAVIA, FAZILA; WAHYUNI, SRI; ANGGRAINI KURNIA, GADIS; RENALDI PUTRA, ETAL (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) Institut Teknologi Bisnis Riau, 2025)
This article discusses the implementation of an employee scheduling information system using Visual Basic Studio 2010 to facilitate work schedule management within a company. The objective of this research is to develop an application that can generate efficient and flexible work schedules while minimizing human errors in schedule planning. The system integrates employee data, work shifts, and the company's operational needs into one easy-to-use platform. The application development uses Visual Basic Studio 2010 as the development environment, with key features such as employee data input, automatic schedule creation, and scheduling reports. The system implementation results show that the application is capable of improving time efficiency, simplifying schedule management, and reducing errors in employee scheduling. Therefore, this system can make a significant contribution to companies in enhancing productivity and employee satisfaction.